La planificación didáctica y su incidencia en el proceso de enseñanza-aprendizaje en los novenos años de educación básica en el área de matemáticas de los centros educativos fiscales de la parroquia Jubones, cantón Machala, periodo lectivo 2013-2014 - Hidalgo Tandazo, Wilson Manfredy (2014)
Planning is a fundamental task in teaching because this depends on the success or otherwise of teaching, plus it allows combining theory and pedagogical practice. Planning becomes a rather mechanical activity, which does not match at all with the development of classes in practice. Planning is very important for teachers because it allows you to join a particular pedagogical theory and practice. It is what makes think coherently sequence of learning to be achieved with students. The key is to understand planning as a "previous model" which allows us to think in teaching that comes from the experience of previous years, in order to improve on future opportunities and not as an imposition. Planning is what you want to do in theory, but not always results in practice. However, not get the desired result does not mean that planning is not good, but there are ways to modify it according to the context in which you work. The importance of planning is rooted in the need to coherently organize what you want to achieve with students in the classroom. This involves taking pre-practice decisions about what they will learn, what will be done and how to achieve the best. You also have to think about the purpose of what we are doing, because it is essential for students to recognize some motivation or encouragement against the new learning. Finally, you should also consider the most appropriate way to work with students, thinking of activities that could convert knowledge into something close and interesting to a group within a given context.